(untitled) (International relations and international law Journal, 2016)
This article is devoted to the features of a legal mechanism for resolving bilateral trade disputes of the CIS countries. The article focuses on the regulatory procedure for resolving such disputes. Studied issue is considered in the framework of two units, based on two different international legal acts of the CIS. Authors analyze the provisions of the Agreement of the CIS member states for establishing a free trade zone in 1994 and the Treaty of the CIS member states on free trade zone in 2011, dedicated to the resolution of interstate trade disputes, in comparative legal perspective. There is a conclusion in the article that the dispute resolution mechanism set forth in Agreement of the CIS member states for establishing a free trade zone in 1994 remains valid, despite the fact that the Agreement itself has lost validity since 2012. Basic elements of the previous agreement were reproduced in the new agreement on free trade zone on October 18, 2011, although the mechanism for resolving disputes under the Agreement in 2011 moved from a rather rigid structure of the Agreement in 1994, which required moving from one alternate dispute resolution process to another. Instead, more liberal and based on the discretion of the Parties order was established.